The Afro-Arab unique hybrid architecture in search for a socio-cultural unification symbolism in the Sudan - Ibrahim, Ahmed Osman (Technium Social Sciences Journal, 2022)
The Sudan, a name derives from the Arabic expression bilad as-sudan meaning the lands of the blacks. Thousands articles cover prominent Pan-African, Afrocentric and Africology theorists and writers who have transparent, bold, and brave advocatory writings uncovering African architecture significance and values including articles of the Sudan’s architecture. The two Pan-African, Afrocentric and Africology theorists and writers who later become Americans; the Kenyan American Ali Mazrui and the Nigerian American Nnamdi Elleh are the most renowned. For the purpose of this research only Public and Governmental Buildings will be taken into consideration as they constitute most of the buildings built for the use of the communities. Evidences for the constructions of the Sudan in form of Public and Governmental Buildings appear in the ancient Kushites mainly as monumental buildings in form of shrines as temples, sanctuaries and burial places as cemeteries and pyramids until the Christian kingdoms who had Cathedrals and Churches as Public and Governmental Buildings. The Mahdist State and the Anglo-Turkish rule of the Sudan had some of their Public and Governmental Buildings in form of Mosques and burial places as the mausoleums (Qubbas). Vernacular architecture in the Sudan, an architecture that characterizes a place by giving it a specific social identity or a sense of belonging and a sense of place reflecting the environmental, cultural and historical context in which it exists. This kind of architecture reflects Ethnicity, Tribalism and Territory, therefore, there is a necessity in the search for an architecture that boosts resolving these socio-cultural problems. Soci-culturally communities all over the world faced with the challenges of the prevailing notions of globalization and Critical Theory that rejects ideology. In the midst of all these challenges of contemporary architecture dominantly adopted in these recent years, the Sudan, thefore, should not be an exception. The objective of this research is to necessarily call for the production of Public and Governmental diversified buildings to boost resolving social problems by adopting Contemporary architecture most precisely Critical Regionalism architecture movement, with other Contemporary architecture movements. The architecture of power and sovereignty such as Public and Governmental buildings could so much assist in reflecting social coherence and unification the Sudanese people should derelict the inferiority feeling in Ethnicity, Tribalism and Territorialism many Sudanese people suffer as a result of producing Public and Governmental in styles other than Critical Regionalism and the like that. Buildings in styles other than Critical Regionalism styles and the like makes people have inferiority feeling for their socio-cultural values in contrary to acquiring unity and coherence feeling. The majority of Sudanese people being of African origin with a good number of Afro-Arabs of different Ethnicity groups, various Tribes and many Territories will not easily come to a consensus in regards to an agreed upon building style that satisfies their socio-cultural differences. The method adopted in coming out with this research is analytical in which the architecture of the Sudan will be traced from the past until the present modern and contemporary architecture to see whether it is in any form has an Afro-Arab hybrid uniqueness in architecture.